Piśmiennictwo religijne Tatarów Wielkiego Księstwa Litewskiego jako oryginalne źródło do badań polszczyzny północnokresowej - Kulwicka-Kamińska, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The religious writings of the Tatars constitute a valuable source for philological research due to the presence of heretofore unexplored grammatical and lexical layers of the north borderland Polish language of the 16th-20th centuries and due to the interference-related and transfer-related processes in the context of Slavic languages and Slavic-Oriental contacts. Therefore the basis for linguistic analyses is constituted by one of the most valuable monuments of this body of writing – the first translation of the Quran into a Slavic language in the world (probably representing the north borderland Polish language), which assumed the form of a tefsir. The source of linguistic analyses is constituted by the Olita tefsir, which dates back to 1723 (supplemented and corrected in the 19th century). On the basis of the material that was excerpted from this work the author presents both borderland features described in the subject literature and tries to point the new or only sparsely confirmed facts in the history of the Polish language, including the formation of the north borderland Polish language on the Belarusian substrate. Research involves all levels of language – the phonetic-phonological, morphological, syntactic and the lexical-semantic levels.